Death without prior appropriate implantable cardioverter-defibrillator therapy: a competing risk study. - Koller, M; Schaer, B; Wolbers, M; Sticherling, C; Bucher, H; Osswald, S (2008)
BACKGROUND: Implantable cardioverter-defibrillators (ICDs) improve survival in selected patients with left ventricular systolic dysfunction in randomized trials. Competing death without prior appropriate ICD therapy might preclude benefit from ICD implantation in a less selected routine-care population. METHODS AND RESULTS: We selected all patients with ischemic or dilated cardiomyopathy with an ICD implanted for primary or secondary prevention from a single-center prospective registry between 1994 and 2006. The end point was time to first appropriate ICD therapy/confirmed ventricular fibrillation or death without prior appropriate ICD therapy. We analyzed cumulative incidence functions and used competing risk regression to study predictors of appropriate ICD therapy or prior death. In 442 patients, 73 deaths occurred during a median follow-up of 3.6 years (maximum, 12.7 years). The cumulative incidence of first appropriate ICD therapy until year 7 was 52%, whereas 11% died without prior ICD therapy. The cumulative incidence of appropriate ICD therapy for ventricular fibrillation was 13%, whereas 23% died without prior therapy for ventricular fibrillation. Appropriate ICD therapy was twice as likely in secondary prevention compared with primary prevention, whereas death rates before ICD therapy were similar in both groups. Diuretic use for heart failure compared with nonuse predicted a 4-fold-increased risk of death prior to ICD therapy, although the incidence of appropriate ICD therapy was similar in both groups. CONCLUSIONS: In a contemporary ICD population, the risk of death without prior appropriate ICD therapy is substantial, especially in patients with advanced heart failure.